4B.04: COST-UTILITY OF ANGIOTENSIN-CONVERTING ENZYME INHIBITOR COMPARED TO THIAZIDE DIURETIC -BASED TREATMENT FOR HYPERTENSION IN ELDERLY AUSTRALIANS CONSIDERING DIABETES AS COMORBIDITY. (June 2015) - Chowdhury, E.; Ademi, Z.; Moss, J.; Wing, L.; Reid, C.
Abstract : Objective: To examine the cost-effectiveness of angiotensin-converting enzyme inhibitor-based (ACEI) treatment compared to thiazide diuretic-based treatment for hypertension in elderly Australians considering diabetes as an outcome along with cardiovascular outcomes from the Australian government perspective. Design and method: We used a cost-utility analysis to estimate the incremental cost-effectiveness ratio (ICER) per quality-adjusted life-year (QALY) gained. Data on cardiovascular events and new-onset of diabetes were used from the Second Australian National Blood Pressure Study, a randomized clinical trial comparing diuretic-based (hydrochlorothiazide) versus ACEI-based (enalapril) treatment in 6083 elderly (age 65yrs or more) hypertensive patients over a median 4.1-year period. For this economic analysis, the total study population was stratified into two groups. Group A was restricted to participants diabetes-free at baseline (n = 5, 642); and Group B was restricted to participants with pre-existing diabetes mellitus (Type I or Type II) at baseline (n = 441). Data on utility scores for different events were used from available published literatures; whereas, treatment and adverse event management cost were calculated from direct health care costs available from Australian Government reimbursement data. Quality of life and costs were discounted at 5% per annum. One-way and probabilistic sensitivity analyses were performed to assess the uncertainty around utilities and cost data. Results: After a treatment period of five years, for Group A the ICER was AUD 27, 698 (Euro 18, 004; AUD 1∼ [Euro sign] 0.65) per QALY gained comparing ACEI-based with diuretic-based treatment (sensitive to the utility value for new-onset diabetes). In Group B, ACEI-based treatment was a dominant strategy (both more effective and cost-saving). On probabilistic sensitivity analysis, the ICERs per QALY gained were always below AUD 50, 000 for Group B; whereas for Group A the probability of being below AUD 50, 000 was 85%. Conclusions: Although the dispensed price of diuretic-based treatment of hypertension in the elderly is lower, upon considering the potential enhanced likelihood of the development of diabetes in addition to the costs of treating cardiovascular disease, ACEI-based treatment may be a more cost-effective strategy in this population.